2017
DOI: 10.1021/acsami.6b15011
|View full text |Cite
|
Sign up to set email alerts
|

Barium Titanate Film Interfaces for Hybrid Composite Energy Harvesters

Abstract: Energy harvesting utilizing piezoelectric materials has become an attractive approach for converting mechanical energy into electrical power for low-power electronics. Structural composites are ideally suited for energy scavenging due to the large amount of mechanical energy they are subjected to. Here, a multifunctional composite with embedded sensing and energy harvesting is developed by integrating an active interface into carbon fiber reinforced polymer composites. By modifying the composite matrix, both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…It was worth noting that O existed not only in BTO NPs, but also in the carbonized nanofiber, which was caused by the oxidation of carbon fiber in the air at 240 o C. planes of crystalline BTO, identical to free BTO NPs. [29][30][31][32] It is noteworthy that the peak splitting at 45 o for (200) and (002) planes indicated that the BTO NPs had a tetragonal phase with piezoelectric effect (Figure 1j). [33][34] PAN-C nanofibers (carbonized PAN nanofibers without BTO NPs) and PAN-C/BTO nanofibers showed similar Raman spectrum patterns with peaks at 1360 cm -1 (defects or heteroatom doping (D-band)), and 1580 cm -1 (crystalline sp2 carbon (G-band)) ( Figure 1K).…”
Section: Resultsmentioning
confidence: 99%
“…It was worth noting that O existed not only in BTO NPs, but also in the carbonized nanofiber, which was caused by the oxidation of carbon fiber in the air at 240 o C. planes of crystalline BTO, identical to free BTO NPs. [29][30][31][32] It is noteworthy that the peak splitting at 45 o for (200) and (002) planes indicated that the BTO NPs had a tetragonal phase with piezoelectric effect (Figure 1j). [33][34] PAN-C nanofibers (carbonized PAN nanofibers without BTO NPs) and PAN-C/BTO nanofibers showed similar Raman spectrum patterns with peaks at 1360 cm -1 (defects or heteroatom doping (D-band)), and 1580 cm -1 (crystalline sp2 carbon (G-band)) ( Figure 1K).…”
Section: Resultsmentioning
confidence: 99%
“…Bowland et al [119] studied the synthesis of BaTiO 3 textured films on carbon fiber fabrics and their integration into a carbon fiber composite with power generation and sensing capabilities. The flexible composite showed an electrical output of 23.5 mV g À1 when excited at its resonant frequency of 96 Hz, and it had a power density of 0.217 nW cm À3 from only 1 g rms acceleration.…”
Section: Non-piezoelectric Polymer With Batiomentioning
confidence: 99%
“…Piezoelectric materials are a class of smart materials that researchers can use to convert mechanical inputs into electrical outputs, or vice versa [10]. They are used in a variety of applications such as actuating, sensing, charging batteries, powering nanodevices, vibrational damping, structural health monitoring, and energy harvesting [5,7,8,[11][12][13][14], and they can also be used as capacitors, inductors, and resonators [13].…”
Section: Piezoelectricitymentioning
confidence: 99%
“…They noted that this was likely due to agglomerations, change in the contact resistance, and excess air voids [6]. These methods are not mutually exclusive, however, and many researchers have chosen to work with composites to implement the advantages of different materials and structures [9,14,26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation